2007
DOI: 10.1186/1471-2164-8-244
|View full text |Cite
|
Sign up to set email alerts
|

Use of tiling array data and RNA secondary structure predictions to identify noncoding RNA genes

Abstract: Background: Within the last decade a large number of noncoding RNA genes have been identified, but this may only be the tip of the iceberg. Using comparative genomics a large number of sequences that have signals concordant with conserved RNA secondary structures have been discovered in the human genome. Moreover, genome wide transcription profiling with tiling arrays indicate that the majority of the genome is transcribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Covariance is present when the identity of a residue at one position in a sequence is at least partially dependent upon the identity of the residue at another position. Covariance has been widely used to evaluate RNA structure (27,34,36,46,69,73) and less extensively to probe intraprotein interactions (26,42,53). We and others recently applied it to the full amino acid coding potential of the hepatitis C virus (HCV) genome (3,11,41).…”
mentioning
confidence: 99%
“…Covariance is present when the identity of a residue at one position in a sequence is at least partially dependent upon the identity of the residue at another position. Covariance has been widely used to evaluate RNA structure (27,34,36,46,69,73) and less extensively to probe intraprotein interactions (26,42,53). We and others recently applied it to the full amino acid coding potential of the hepatitis C virus (HCV) genome (3,11,41).…”
mentioning
confidence: 99%
“…It is known that most of the genome is transcribed in complex patterns of interacting and overlapping transcripts from both strands ( 5–9 ), and most mammalian genes also have antisense transcripts ( 7 , 9–11 ). We currently have a great deal of information ( 4 , 5 , 12–14 ) arising from modern technologies, such as tiling arrays, that confirm the genome to be pervasively transcribed, and that the noncoding regions, such as the introns and intergenic regions, play an important role in human genome regulation by cis -acting at the transcriptional level ( 4 , 15 , 16 ). These approaches have resulted in the discovery of many novel transcribed sequences, and provide a new perspective on the number and extent of transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental evidence in mammals has indicated that the portion of the genome that is transcribed, as well as the number of functional RNAs in the genome, is much higher than previously thought [1][10]. Functional RNAs include noncoding RNAs as well as cis-acting RNA elements within mRNAs.…”
Section: Introductionmentioning
confidence: 99%